Compliance to Hypertension Treatment in Residents of a Fishermen Colony in District Kollam, Kerala - Ahmad Nadeem Aslami and Abraham Jobby (Nepal J Epidemiol., 2015)
Background: Hypertension is an important underline cause for cardiovascular deaths worldwide. Treatment compliance for hypertension depends on a lot of factors. There is paucity of studies about awareness and compliance to antihypertensive treatment particularly in coastal areas. Our aim was to know the awareness, treatment, compliance and control of blood pressure among hypertensive patients in a fishermen colony of Jonakapuram, Kollam. Material and Methods: A community based cross sectional study was done in a coastal area of Kollam. A house-to-house survey was conducted with a pretested semi-structure questionnaire. Three blood pressure readings were taken and mean value was calculated. The study period was one year. Data was analyzed by using Statistical Package of Social Sciences 12. Appropriate statistical tests were applied. Results: A total of 276 persons were found to be hypertensive. The percentage of awareness, treatment among aware subjects, treatment compliance and control of BP among patients taking anti-hypertensives was 71.74%, 85.86%, 73.53% and 50.58%. The awareness and treatment was significantly more among females as compared to males. The advices received by the patients were medicines, diet restrictions and lifestyle changes. Financial problems were the main reason for non-compliance to medicines. Conclusion: Nearly 3/4 th of the study subjects were aware that they have hypertension. Monetary problems were an important cause for non-compliance. Half of the patients taking antihypertensive medication had their blood pressure uncontrolled. Patient’s economic status should be considered before advising them medications. This will increase compliance and help in improving the quality of patient care.